Studi Kestabilan Generator Sistem Sulselrabar - Muhammad Ruswandi Djalal; Faisal Faisal (Muhammadiyah University, Sidoarjo, 2019)
In the standard operating system, the input parameters such as changes in the mechanical torque of the turbine and changes in the field voltage of the amplifier from the exciter need to be considered. Some studies that can be done include the study of the dynamic stability of synchronous generators when dealing with small changes that occur using the eigenvalue approach which is the roots of the characteristic equations of the system state space equation. The eigenvalue can show information on system stability and is related to the response of time to changes in the system. The system used is in the Sulselrabar electrical system. From the simulation results show the characteristics of the system in terms of the frequency response and angle of the generator rotor. For the eigenvalue system value in the inter-area oscillation mode is -0.33293 + 4.0844i, for the oscillation mode it is -0.9043 + 7.9670i. While the generator frequency response, where oscillations occur before reaching steady state conditions. The biggest overshoot response occurs in Old Tello plants, with a maximum overshoot of 0.09124 pu and a minimum of -0.2227 pu. While the smallest overshoot response is found in the Bakaru hydroelectric power plant which is equal to 0.004681 maximum pu and -0.02563 minimum pu.